2020
DOI: 10.3390/jcm9041071
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Milking in Infants Born at <37 Weeks of Gestation: A Systematic Review and Meta-Analysis

Abstract: Umbilical cord milking (UCM) could be an alternative in cases where delayed umbilical cord clamping cannot be performed, therefore our objective was to evaluate the effects of UCM in newborns <37 weeks’ gestation. In this systematic review and meta-analysis, we searched MEDLINE, EMBASE, CINAHL, the Cochrane Database of Clinical Trials, the clinicaltrails.gov database for randomized UCM clinical trials with no language restrictions, which we then compared with other strategies. The sample included 2083 prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…There has been no significant decrease in mortality identified in comparisons of UCM vs. ECC [18,29]. One meta-analysis comparing UCM to both ECC and DCC in < 37-week preterm infants found the additional risk of RDS with UCM [30]. These analyses are complicated by variable times to onset of breathing and different UCM strategies, resulting in differential placental transfusion and stability of cerebral perfusion.…”
Section: Umbilical Cord Milkingmentioning
confidence: 99%
“…There has been no significant decrease in mortality identified in comparisons of UCM vs. ECC [18,29]. One meta-analysis comparing UCM to both ECC and DCC in < 37-week preterm infants found the additional risk of RDS with UCM [30]. These analyses are complicated by variable times to onset of breathing and different UCM strategies, resulting in differential placental transfusion and stability of cerebral perfusion.…”
Section: Umbilical Cord Milkingmentioning
confidence: 99%
“…Doğum sonrası göbek kordonunun klemplenme zamanı veya kordun sağılmasıyla ilgili çalışmalarda; geç kord klemplemenin Htc ve serum ferritin düzeylerini arttırdığı, mortaliyeti ve İVK riskini azalttığı, kan transfüzyonunda %10 azalma sağladığı, ancak kord sağmanın aşırı prematüre (<28 gebelik haftası) bebeklerde ciddi İVK riskini arttırdığı, hatta bazı çalışmalarda RDS riskini arttıryor gözüktüğü belirtilmekte olup, prematüre bebeklerde ideal kord uygulama yönteminin halen net olarak ne olduğununu bilinmediği, ancak erken kord klemplemenin (<30 sn) prematüre bebeklerde zararlı olabileceği nedeniyle bu bebeklere erken kord klemplemenin önerilmemesi gerektiği bildirilmektedir [6,[33][34][35][36][37][38][39][40]. Kord sağma işlemi prematüre bebeklerde serebrovasküler ve sistemik kan akımında fluktuasyonlara neden olabileceği için şu an önerilmemektedir [10].…”
Section: Non-farmakolojik öNlemlerunclassified
“…This cord management is considered to enhance placental-to-fetal transfusion and could be a suitable alternative placental transfusion method for delayed cord clamping if a newborn infant requires resuscitation in the delivery room to avoid delayed resuscitation[ 2 ]. Some clinical trials and meta-analyses have suggested benefits of UCM vs immediate cord clamping without apparent complications[ 3 ]. It has been adopted at some tertiary neonatal centers, especially for late preterm or term infants, to increase iron levels and prevent the development of iron deficiency anemia, which is associated with impaired motor development, behavioral problems, and cognitive delays[ 4 ].…”
Section: Introductionmentioning
confidence: 99%